Manual Therapy: The Historical, Current, and Future Role in the Treatment of Pain - A. Russell Smith (The Scientific World Journal)
Manual therapy has been an approach in the management of patients with various disorders dating back to ancient times and continues to play a significant role in current health care. The future role of manual therapy in health care is an important area of research. This paper reviews the history of manual therapy, examines the current literature related to the use of manual techniques (including manipulation, massage, and nerve manipulation), and discusses future research topics. The literature related to manual therapy has historically been anecdotal and theoretical, and current research tends to have a generic approach with broad definitions of manual therapy and inconsistencies in the classification of specific disorders. Systematic reviews of various types of manual therapy have differed on their conclusions regarding the effectiveness of this treatment modality. The current demand in health care for evidence-based practice necessitates a movement towards more specificity in the research of the effectiveness of manual therapy, with emphasis on specific patient signs and symptoms and specific manual techniques that result in effective care.